2001
DOI: 10.1007/s001090100265
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E gene promoter (–219G/T) polymorphism is associated with premature coronary heart disease

Abstract: The relationship of two apolipoprotein (apo) E gene polymorphisms and coronary heart disease (CHD) was investigated in 118 Finnish families with premature CHD and in 110 healthy control subjects. Affected siblings and probands with premature CHD had higher frequencies of the T allele of the -219G/T promoter polymorphism and the epsilon 4 allele (genotypes epsilon 4/3 or epsilon 4/4) of the apo epsilon 2/epsilon 3/ epsilon 4 polymorphism than those of healthy control subjects. Additionally, when the two apo E g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 16 publications
4
17
1
Order By: Relevance
“…The frequencies of the 2219G and 2219T alleles were 0.62 and 0.38, respectively, and those of the 1113G and 1113C alleles were 0.63 and 0.37. The promoter genotype distributions were in Hardy-Weinberg equilibrium and similar to those seen in previous Finnish studies (1,17,18). Age, BMI, systolic or diastolic blood pressure, and smoking did not differ significantly between the APOE promoter genotype groups in the e3/e3 carriers ( Tables 1, 2).…”
Section: Characteristics Of the Study Populationsupporting
confidence: 85%
“…The frequencies of the 2219G and 2219T alleles were 0.62 and 0.38, respectively, and those of the 1113G and 1113C alleles were 0.63 and 0.37. The promoter genotype distributions were in Hardy-Weinberg equilibrium and similar to those seen in previous Finnish studies (1,17,18). Age, BMI, systolic or diastolic blood pressure, and smoking did not differ significantly between the APOE promoter genotype groups in the e3/e3 carriers ( Tables 1, 2).…”
Section: Characteristics Of the Study Populationsupporting
confidence: 85%
“…12 Moreover, the À219G/T polymorphism has been reported to associate with atherogenic lipid and lipoprotein profile, 13,14 as well as with coronary atherosclerosis. 15 However, the role of these SNPs in IS and in cerebral atherosclerosis has not been studied before.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have suggested that the APOE ε2/ε3/ε4 polymorphism may modify the effect of insulin on CHD or some CHD risk factors, including obesity and lipid profile levels (Després et al, 1993;Valdez et al, 1995;Elosua et al, 2003), whereas the Framingham Offspring Study and Turkish Adult Risk Factor (TARF) Study found that this polymorphism was not associated with insulin resistance (Meigs et al, 2000;Komurcu-Bayrak et al, 2011). Two other of the functional SNPs, i.e., -219G>T (rs405509) and +113G>C (rs440446) in APOE gene had shown association with plasma apoE concentrations (Lambert et al, 2000;Moreno et al, 2003), insulin resistance (Viitanen et al, 2001), insulin sensitivity in response to a diet rich in satured fats (Moreno et al, 2005). In a cross-sectional study, the impacts of these polymorphisms have been analyzed on lipid, apolipoprotein, glucose, and serum insulin concentrations in the TARF cohort, a representative of Turkish adults.…”
Section: The Polymorphisms Of the Apoe Genementioning
confidence: 99%